PENGUATAN LEMBAGA KELOMPOK PENGOLAH DAN PEMASAR (POKLAHSAR) PRODUK HASIL PERIKANAN DAN KELAUTAN DI KOTA TEGAL - Yusuf, Muhammad; Nurhayati, Atikah; Handaka Suryana, Asep Agus; Pamungkas, Wahyuniar; Prihadi, Donny Juliandri (Jurnal Pengabdian Perikanan Indonesia, 2025)
Tegal City has significant potential in the fisheries and marine sector, which can be utilized as a source of livelihood for the community and to drive regional economic growth. To optimize this potential, the Tegal City Department of Maritime Affairs and Fisheries, Agriculture, and Food, through the Fisheries Division, implemented a program to strengthen the Processing and Marketing Group (POKLAHSAR) institution. This assistance aimed to describe the process of establishing POKLAHSAR, provide training on fishery product processing, assist in obtaining business permits, and provide supporting facilities to increase the group's capacity and independence. The method used consisted of four stages: POKLAHSAR formation, training, licensing assistance, and providing supporting facilities. The results of the activity indicate that POKLAHSAR formation was carried out in a structured manner through group legalization, as well as obtaining legal entities and business permits. The fishery product processing training successfully improved members' skills in producing value-added processed products, while licensing assistance facilitated the group's acquisition of business legality and product distribution permits. The provision of supporting facilities can improve product efficiency and quality. The POKLAHSAR strengthening program in Tegal City can enhance group capacity and positively impact community economic development, particularly in the fisheries sector.